PEMBELAJARAN TARI KREASI MELALUI PROJECT BASED LEARNING UNTUK MEMBANGUN KARAKTER SISWA SMAN 1 GARUT - Gisel Tanjung Oktarina Dwi Pratiwi, - (2018)
This study aims to improve the character of students of SMAN 1 Garut, especially in respect, creative and confident through creation dance learning using project based learning. In the implementation process, used the steps of composition theory such as exploration, improvisation, evaluation and composition. The learning method that is implemented at each meeting uses a project based learning by the steps start with the essential question, design a plan for the project, create a schedule, monitor the students and the progress of the project, and evaluate the experience. The research method used is an experimental method with a quantitative research paradigm. The results of this study prove the hypothesis that the learning of creation dance using project based learning can build the character of students of SMAN 1 Garut to respect each other, creative, and confidence. Obtaining an pretest score of67 and increase after being given treatment obtained an posttest score 81. The results of this study are expected to be a reference for the use of dance learning methods and materials in high school education, and can be an idea of developing art learning methods dance for further research.